Kampanye Public Relations dalam Mensosialisasikan Mitigasi Bencana - Azhar, Deanira Permata (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2023)
This study aims to describe the process of a public relations campaign in socializing disaster mitigation carried out by the Regional Disaster Management Agency of West Java Province. The researcher describes the process of a public relations campaign starting from problem identification, planning, implementation, and evaluation. This study uses a public relations campaign model from Leon Ostegaard. The paradigm used in this research is constructivism. The approach used is qualitative. The method used in this research is descriptive analysis. Data collection techniques used were in-depth interviews and passive participant observation.